Genetic parameters associated with meat quality of Nellore cattle at different anatomical points of longissimus: Brazilian standards. (January 2021) - de Nadai Bonin, Marina; Pedrosa, Victor Breno; da Luz e Silva, Saulo; Bünger, Lutz; Ross, Dave; da Costa Gomes, Rodrigo; de Almeida Santana, Miguel Henrique; de Córdova Cucco, Diego; de Rezende, Fernanda Marcondes; Ítavo, Luís Carlos Vinhas; de Novais, Francisco José; Pereira, Marília Williani Filgueira; et al.
Abstract: The present study estimated genetic parameters and evaluated the genetic and phenotypic correlations between meat quality characteristics of Nellore cattle evaluated at different anatomical points of the longissimus. Data from 1329 Nellore young bulls were used to evaluate, in the 5th and 12th ribs, marbling score (MAR), shear force (SF), cooking weight losses (CWL) and intramuscular fat (IMF). In addition, the subcutaneous fat thickness was measured at the 12th rib (SFT12 ) and between the last lumbar and the first sacral vertebrae (SFTLR ), in the separation of loin and round. Results yielded moderate heritability coefficients for evaluated characteristics, except CWL. High genetic correlations (0.61) were found between measurements of SFT12 and SFTLR . MAR, IMF and SF were evaluated at the 5th and 12th rib. Meat quality and subcutaneous fat thickness measured at different anatomical points of the longissimus are genetically correlated and can be used in genetic selection programs to improve meat quality characteristics in Nellore cattle.